Montara Well Release: Olfactory analysis of Timor Sea fish fillets - Rawson, Christopher; Gagnon, Marthe Monique; Williams, Hannah (Department of Sustainability, Environment, Water, Population and Communities, 2011)
This report was prepared by Christopher Rawson and Marthe Monique Gagnon from the Department of Environmental and Agriculture, Curtin University and Hannah Williams from the Food Science & Technology Program, School of Public Health, Curtin University. This report describes the results of the olfactory analysis of fish samples collected in the Timor Sea following the Montara well release. The olfactory analysis was conducted in March 2011, in the Sensory Evaluation laboratories located in the School of Public Health, Curtin University.